2022
DOI: 10.1177/14680173221109687
|View full text |Cite
|
Sign up to set email alerts
|

Indigenised approaches to addressing elder abuse in Uganda

Abstract: Summary The social gerontological field has long called for a culturally appropriate framework to understand, prevent, and respond to elder abuse in the Global South. This emphasis is, in part, based on the notion that elder abuse is a cultural and structural concern that cannot be effectively addressed using mainstream social work approaches. Therefore, indigenised approaches are preferred while tackling cultural and structural forms of elder abuse. However, despite several attempts, there is limited research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…The study targeted the opinions of a population of 437 respondents who included caregivers, probation offices, community development officers, police, local leaders, religious leaders and CSOs in Kisoro, Rukiga, Rukungiri, Bushenyi and Mbarara districts in Southwestern Uganda. The districts were chosen because studies have indicated that instances of poor welfare of older persons had been on the rise (Atim et al , 2023; Wamara et al , 2022). The above respondents who formed the unit of analysis were chosen because they on a daily basis work with the elderly persons, know their challenges and hence were much suited to provide appropriate responses for this study.…”
Section: Methodsmentioning
confidence: 99%
“…The study targeted the opinions of a population of 437 respondents who included caregivers, probation offices, community development officers, police, local leaders, religious leaders and CSOs in Kisoro, Rukiga, Rukungiri, Bushenyi and Mbarara districts in Southwestern Uganda. The districts were chosen because studies have indicated that instances of poor welfare of older persons had been on the rise (Atim et al , 2023; Wamara et al , 2022). The above respondents who formed the unit of analysis were chosen because they on a daily basis work with the elderly persons, know their challenges and hence were much suited to provide appropriate responses for this study.…”
Section: Methodsmentioning
confidence: 99%